Burnout Among Health Workers and Recommendations After the Covid-19 Pandemic - Jasman Jasman; Fibria Indriati (Khazanah Sosial, 2023)
This study aims to analyze the ideal efforts to overcome burnout among health workers and recommendations after the Covid-19 pandemic. The research was conducted using a qualitative approach with data collection techniques in the form of documentation studies. Results The documentation study found that health workers faced various pressures during their service during the COVID-19 pandemic. Burnout occurs because of an imbalance between abilities, skills and available resources with the needs and demands of the job. Burnout is recognized as a problem in all healthcare systems. So that in addition to its adverse effects on the physical and mental health of personnel, fatigue reduces efficiency, organizational commitment, self-esteem, civic behavior, creativity, innovation, and quality of nursing services. On the other hand, it can increase the hospital's financial burden, frustration, disappointment, dissatisfaction and result in deviant, destructive behavior and turnover.